Awareness on online financial scam: A study in Malaysia - Lee, Wen Xian; Lim, Nya Hia; Lim, Vivian Yan Yi (2023)
This research aims to identify the awareness on online financial scam in Malaysia by using Technology Threat Avoidance Theory (TTAT) and Theory of Planned Behaviour (TPB). Independent variables included are cybersecurity knowledge, perceived severity, subjective norm, as well as security and privacy concern. The data collection method in this research is primary data and 384 sets survey questionnaires were collected. Partial Least Square Structural Equation Modelling (PLS-SEM) software was used to generate statistical analysis. The results showed that cybersecurity knowledge, perceived severity, and subjective norm have significant relationship with the awareness on online financial scam; while security and privacy concern has insignificant relationship with the awareness on online financial scam. This research will provide an insight for Malaysian, companies, and policymaker to better understand the ways to increase awareness on online financial scam. Limitations and recommendations are provided in this research for future researchers to have a better understanding in conducting future research.